Expressing national identity: national issues from the Indonesian Muslim diaspora - Hartimah, Tati; Farlina, Nina; Sulaiman, Setyadi; Garadian, Endi Aulia (Faculty of Communications Science, Dr. Soetomo University, 2025)
Abstract This study analysed how Indonesian Muslim diasporas utilise social media to express their national identity. This research employed a qualitative approach, utilising the symbolic interaction theory of G.H. Mead and virtual ethnographic analysis to examine the Indonesian Muslim diaspora's activity on Twitter (now known as X) to maintain an intense connection with Indonesian public discourse through actively posting their notion on the platform. The research discovered that several Indonesian Muslim diasporas who are active on Twitter have experienced intimidation because of their tweets. Twitter, which should be a free space to express opinions, has become a space of judgment. Tweets that criticise social, political, economic and religious issues affect their lives; they are threatened, intimidated, and dehumanised in various ways, and their space is restricted. Not only on national issues but intimidation also applies when they respond to international issues, such as the Palestine conflict. Their activism in tweeting about Palestine resulted in the termination of their work contracts and ostracisation in academic circles in Europe. This research shows the critical role of Twitter as a medium for disseminating national ideas and ideas that strengthen the national identity of the Indonesian Muslim diaspora. They leverage social media for digital activism, shaping national identity, democracy, and governance. Their participation extends beyond discourse into transnational political engagement, where they construct counter-public and intersectional narratives that challenge dominant perspectives. Through these digital spaces, they contribute alternative viewpoints on socio-political issues, influencing both national and international discussions.